Sri Aurobindo's Principles, Philosophy, Nationalism And Education: A Critique (Journal of Namibian Studies : History Politics Culture, 2023)
Sri Aurobindo is a great educationist, philosopher and nationalist.  He has made an extremely special contribution to the subject of education. In real-world applications, he combines Western and Indian philosophy. We move from materialism to spiritualism with his life philosophy. In the sphere of Indian education, Sri Aurobindo's philosophical ideas are unique. By fostering individual virtue through education, he hopes to make Indian society just and content. In this article, Sri Aurobindo’s principles, philosophy, nationalism and education has been discussed.